Wood Specific Gravity in Stem and Branches of Eleven Timbers from Kerala - Bhat, K. M.; Bhat, K. V.; Dhamodaran, T. K. (Indian Forester, 1990)
Wood specific gravity of stem and branches was compared in eleven selected timber species. No significant difference existed between stem and branch values with the exception of cashew and dillenia; the branch wood being heavier in the former and lighter in the latter. Specific gravity of branch wood was correlated with that of stem wood in some species suggesting that at least in certain species stem wood value could be predicted from branch wood specific gravity.